Mindfulness-based stress reduction combined with early cardiac rehabilitation improves negative mood states and cardiac function in patients with acute myocardial infarction assisted with an intra-aortic balloon pump: a randomized controlled trial - Wu, Kemei; Wan, Miaomiao; Zhou, Huiqin; Li, Cui; Zhou, Xiaomin; Li, E.; Li, Ying; Liu, Chengwei; Liu, Li (Frontiers in Cardiovascular Medicine, 2023)
Objective To investigate the clinical effects of mindfulness-based stress reduction (MBSR) intervention combined with early cardiac rehabilitation (CR) on patients with acute myocardial infarction (AMI) assisted with an intra-aortic balloon pump (IABP). Methods A total of 100 AMI patients with IABP assistance due to hemodynamic instability at Wuhan Asia Heart Hospital were enrolled in the study. The participants were divided into two groups using the random number table method (n = 50 each group). Patients receiving routine CR were assigned to the CR control group, while patients receiving MBSR plus CR were assigned to the MBSR intervention group. The intervention was performed twice a day until the removal of the IABP (5–7 days). Each patient's level of anxiety/depression and negative mood state were evaluated before and after intervention using the self-rating anxiety scale (SAS), self-rating depression scale (SDS), and profiles of mood state scale (POMS). The results of the control and intervention groups were compared. IABP-related complications and left ventricular ejection fraction (LVEF), measured with echocardiography, were also assessed and compared between the two groups. Results The SAS, SDS, and POMS scores were lower in the MBSR intervention group than in the CR control group (P < 0.05). There were also less IABP-related complications in the MBSR intervention group. LVEF was significantly improved in both groups, but the degree of LVEF improvement was more significant in the MBSR intervention group than in the CR control group (P < 0.05). Conclusions MBSR combined with early CR intervention can assist in alleviating anxiety, depression, and other negative mood states, reduce IABP-related complications, and further improve cardiac function in AMI patients with IABP assistance.